İsmet’i Divanı’nın tahlili - Söğüt, Tülay (My University, 2003)
17. yüzyıl, Osmanlı Devleti'nin siyâsî, idârî ve sosyal hayatında türlü çalkantı ve karışıklıkların yaşanmasına karşılık, kendisini etkili bir şekilde hissettiren bu olumsuz durumun henüz edebiyâta yansımadığı bir devir olmuştur. 16. yüzyılda, Osmanlı Devleti'nin kazandığı ihtişâma paralel olarak olgunluğa erişmiş olan Dîvan şiiri, bu yüzyılda da gelişmesini sürdürmüş ve pekçok değerli şâir yetişmiştir. Bu yüzyılda Sebk-i Hindi tesiriyle gazeller yazan sanatkârlar yetişmiştir. Birçok dinî-sofiyâne eserler, evliyâ menkıbeleri yazılmıştır. Nef'î, Nâbî, Şeyhülislâm Yahyâ ve Nâilî gibi kaside ve gazel vâdisinde birer zirve olmuş şahsiyetlerle aynı dönemde yetişen diğer bir şâir de 'İsmetî'dir. Bütün bu gelişmelere, Türk şâirlerinin Acem şâirlerini yer yer geçtiklerini belirtmelerine ve bu yolda güzel örnekler vermelerine rağmen, Örfî-i Şirâzî, Tâlib-i Amûdî, Zuhûrî, Muhteşem-i Kâşânî, Sâib-i Tebrizî ve Şevket-i Buharî gibi İran şâirlerinin Dîvan şiirimiz üzerindeki tesirlerinin bu yüzyılda da devam ettiği görülür. Dîvan edebiyâtımız hakkında yeterli seviyede bilgi edinilebilmesi daha iyi anlaşılabilmesi ve yeni kuşaklara anlatılabilmesi için, bu edebiyatımıza ait eserlerin tahlîl ve şerh yoluyla değerlendirilmesi ve değişik yüzyıllarda yaşamış sanatkârların eserlerinden elde edilecek sonuçların karşılaştırılmasına bağlıdır. Dîvan edebiyatımız, altı yüz yılı aşan bir zaman dilimi içinde ortaya koyduğu eserleri ile kültür târihimizin ihmâl edilemeyecek bir bölümüdür. Bu sebepten onların değerlendirilip, tanıtılması ilmî bir mecburiyettir. Her sanat eseri, devrinin fikir, sanat ve güzellik anlayışının birer aynasıdır. Sanatkârı yaşadığı cemiyetten ayrı düşünmek mümkün olamayacağına göre, onun eserinde yaşadığı dönemin sosyal hayatının yansımalarını bulmak oldukça doğaldır. Bunun yanında sanatkârların edebiyât târihi içinde hakîki yerlerini alabilmeleri için eserlerinin tahlîli gerekmektedir. Bunun sonucunda sanatçının topluma bakış açısı, toplum sorunlarıyla ilgilenişi, sosyal hayatı eserlerine yansıtması, edebî kişiliği tespît edilecektir. Sanatçı, toplumun aynası olma özelliğine sahip olduğuna göre bu aynada şâirin yansıttığı bir toplum yaşamının izlerini bulabileceğiz. Ancak bu şekilde kendi içinde ve yaşadığı dönemlerdeki sanatçılarla mukâyese edilmesi mümkün olacaktır. Biz de buna inandığımız için 17. yüzyılda yaşamış ve edebiyâtımıza mürettep bir dîvan kazandırmış olan 'İsmetî'nin Dîvan-ı 'İsmetî adlı eserini tahlîl etmeye çalıştık. Hazırlamış olduğumuz tezimizde bizden önce yapılan değerli çalışmalardan da yararlandık. 17.yüzyılda yetişen 'İsmetî'nin Dîvanı'nın tahlîli olan bu çalışmayı hazırlarken her beyit tek tek incelenmiş, malzemeler belirlenerek tek tek fişlenmiştir. I. Din ve Tasavvuf, II.Cemiyet, III.İnsan ve IV. Tabiat olmak üzere konularına göre tasnif edilerek değerlendirilmiştir. Değerlendirme esas olan örnek beyitler değerlendirme metninin içine alınmış, örnek olarak zikredilmeyen beyitlerin numaraları eserin sonuna ilâve edilen indekste ve metin açıklamaları verilerek cümle sonlarında numaraları verilmek sûretiyle gösterilmiştir. Bu indekste ve cümle sonunda yer alan maddelerin karşısındaki numaralar, bu tezin içinde sayfa numaraları değil, 'İsmetî Dîvanı'nın matbu nüshâsındaki beyitlerin numaralarıdır. Numaraların başında yer alan K kaside, G gazel, R rubâi, S sayfa ve bazı beyitlerin numaralarının en sonundaki B ise beyit numarasını ifâde etmek için kullanılmıştır. Tek beyit halindeki manzûmeler ise sayfa numaraları ve beyit numaraları ile birlikte yine matbu nüshâsındaki sayfa numaralarına ve beyit numaralarına göre verilmiştir. Bu kısaltmalardan sonraki sayı manzûmenin Dîvan içindeki sıra numarasını, en sonda yer alan sayı ise o beyitin manzûme içindeki numarasını ihtivâ etmektedir. İndekste maddelerin karşısında sıralanmış olan numaralar sadece o kelimeyi değil, beyitte o kelime geçmemiş olsa bile o kelimenin ihtivâ ettiği anlamı taşıyan beyitlerin numaralarını da, yani isti'âre veya teşbîh sanatlarıyla veya diğer yollarla mazmûnlaşmış ifâdeleri de kapsamaktadır. Daha yolun başında olduğumun şuuruyla yaptığım bu çalışmamda, olmasına özen göstermekle birlikte beraber ortaya çıkabilecek olan hata ve eksiklerimin mâzur görülmesini ümit ediyorum. Öncelikle çalışmamda bana rehber olan, tezimin sorumluluğunu üstlenen çok değerli hocam Doç. Dr. Sebahat DENİZ'e sonra da çalışmalarımda benden desteklerini esirgemeyen sevgili aileme teşekkürü borç bilirim. Tülay SÖĞÜT İstanbul, 2003 Although 17th century was a century in which all kinds of chaos and disorder was experienced in the political administrative and social life of the Ottoman State, it was still a period in which this negative situation had not reflected upon literature, yet. Divan Poetry which reached its prime of life in parallel with the magnificence gained by the Ottoman State in 16th century, continued its development in this century too, and produced many valuable poets. Artists who were writing gazels with the influence of Sebk-i Hindi sufficed in this century. Many works on religious-sufism and hagiography were written. Another poet who was grown up among the monuments of hall of fame of gazel and kaside like Nef'î, Nâbî, Sheikh al-Islâm Yahyâ is 'İsmetî'. Despite all these developments and the statements that the Turkish poets had gone ahead of Persian poets and presenting nice examples in this manner, it is observed that the influence of Persian poets like Örfî-i Şirâzî, Tâlib-i Amûdî, Zuhûrî, Muhteşem-i Kâşânî, Sâib-i Tebrizî and Şevket-i Buharî continued on our divan Poetry. In order to get adequate information on our Divan literature, to comprehend Divan Literature and to convey to new generations, the works belonging to this literature should be assessed through analysis and interpretation and comparisons should be made with the works of artists lived in different centuries. Divan literature is an essential part of our cultural heritage with the works that it presented throughout more than six centuries, which should not be ignored. Therefore it is a scientific necessity to evaluate it and introduce it. Each work of art is a reflection of the understanding of ideology, art and aesthetics of its period. Since the artist cannot be isolated from the society within which he/ she is living in, it is natural to observe the reflections of the social life of the period in the work of art. Along with this, in order to grant the artist the places they deserved in literary history, these works should be analyzed. As a result of this, the point of view of the artist towards society, his/ her interest in the problems of society, his/ her reflection of the social life to his/ her works, and literary personality will be determined. Since the artist has a characteristic to be the mirror of the society, we will be able to find the tracks of the social life of the artist in the works. Only this way it would be possible to provide a comparison with other artists of the same and other periods. Since we believe in this idea, we tried to analyze Ismeti's Dîvan-ı Ismetî, which is a concise divan. We made use of the valuable studies conducted before in our thesis. During the process of preparing this study, each couplet was analyzed and the materials specified one by one and catalogued. The material was categorized into four groups, namely, I. Religion and Sufism, II. Society, III. Human and IV. Nature, and evaluated in this manner. The couplets which consist the basis for assessment are taken in the text, however other couplets which are not mentioned in the text are presented in the index with their proper reference numbers which are put at the end of the relevant sentence. The reference numbers at the end of the sentences and in the index are not the page numbers in this thesis, but they are the numbers of the couplets in the printed version of 'İsmeti Dîvanı'. The capitals before the numbers used to refer references as in K to kaside, G to gazel, R to Rubai, S to sayfa (page) and the letter B is used after some of the numbers to indicate the number of the couplet. The verse with only a single line are given with the page numbers and couplet numbers as in the printed version of the work. The number after these abbreviations indicate the list number of the verse in the divan and the number at the very end indicates the number of the couplet in that verse. The numbers which are listed in the index opposite to a certain word indicate not only the couplets that mention the word itself but also the couplets which contain the meaning of the same word. In other words, the numbers also indicate the couplets in which that certain word is referred by a simile or a metaphor. With the conscious that I am at the very beginning of this path, and despite my deep concerns to avoid, I would kindly ask forgiveness and tolerance for the possible mistakes that may occur in this text. My deepest gratitude firstly goes to my Ass. Prof. Sebahat DENİZ who guided me in my studies and who carried the responsibility for my thesis and then to my family who supported me during the whole process. Tülay SÖĞÜT İstanbul, 2003 Although 17th century was a century in which all kinds of chaos and disorder was experienced in the political administrative and social life of the Ottoman State, it was still a period in which this negative situation had not reflected upon literature, yet. Divan Poetry which reached its prime of life in parallel with the magnificence gained by the Ottoman State in 16th century, continued its development in this century too, and produced many valuable poets. Artists who were writing gazels with the influence of Sebk-i Hindi sufficed in this century. Many works on religious-sufism and hagiography were written. Another poet who was grown up among the monuments of hall of fame of gazel and kaside like Nef'î, Nâbî, Sheikh al-Islâm Yahyâ is 'İsmetî'. Despite all these developments and the statements that the Turkish poets had gone ahead of Persian poets and presenting nice examples in this manner, it is observed that the influence of Persian poets like Örfî-i Şirâzî, Tâlib-i Amûdî, Zuhûrî, Muhteşem-i Kâşânî, Sâib-i Tebrizî and Şevket-i Buharî continued on our divan Poetry. In order to get adequate information on our Divan literature, to comprehend Divan Literature and to convey to new generations, the works belonging to this literature should be assessed through analysis and interpretation and comparisons should be made with the works of artists lived in different centuries. Divan literature is an essential part of our cultural heritage with the works that it presented throughout more than six centuries, which should not be ignored. Therefore it is a scientific necessity to evaluate it and introduce it. Each work of art is a reflection of the understanding of ideology, art and aesthetics of its period. Since the artist cannot be isolated from the society within which he/ she is living in, it is natural to observe the reflections of the social life of the period in the work of art. Along with this, in order to grant the artist the places they deserved in literary history, these works should be analyzed. As a result of this, the point of view of the artist towards society, his/ her interest in the problems of society, his/ her reflection of the social life to his/ her works, and literary personality will be determined. Since the artist has a characteristic to be the mirror of the society, we will be able to find the tracks of the social life of the artist in the works. Only this way it would be possible to provide a comparison with other artists of the same and other periods. Since we believe in this idea, we tried to analyze Ismeti's Dîvan-ı Ismetî, which is a concise divan. We made use of the valuable studies conducted before in our thesis. During the process of preparing this study, each couplet was analyzed and the materials specified one by one and catalogued. The material was categorized into four groups, namely, I. Religion and Sufism, II. Society, III. Human and IV. Nature, and evaluated in this manner. The couplets which consist the basis for assessment are taken in the text, however other couplets which are not mentioned in the text are presented in the index with their proper reference numbers which are put at the end of the relevant sentence. The reference numbers at the end of the sentences and in the index are not the page numbers in this thesis, but they are the numbers of the couplets in the printed version of 'İsmeti Dîvanı'. The capitals before the numbers used to refer references as in K to kaside, G to gazel, R to Rubai, S to sayfa (page) and the letter B is used after some of the numbers to indicate the number of the couplet. The verse with only a single line are given with the page numbers and couplet numbers as in the printed version of the work. The number after these abbreviations indicate the list number of the verse in the divan and the number at the very end indicates the number of the couplet in that verse. The numbers which are listed in the index opposite to a certain word indicate not only the couplets that mention the word itself but also the couplets which contain the meaning of the same word. In other words, the numbers also indicate the couplets in which that certain word is referred by a simile or a metaphor. With the conscious that I am at the very beginning of this path, and despite my deep concerns to avoid, I would kindly ask forgiveness and tolerance for the possible mistakes that may occur in this text. My deepest gratitude firstly goes to my Ass. Prof. Sebahat DENİZ who guided me in my studies and who carried the responsibility for my thesis and then to my family who supported me during the whole process. Tülay SÖĞÜT İstanbul, 2003
Keywords: Edebiyat; Osmanlıca edebiyat; Osmanlıca şiir (Divan şiiri); Türk Edebiyatı